Decision Support System for Selection of Achieving Student Using Weighted Product Method in SMA XYZ - Nugroho, Imam Ma'ruf; Dewi Lestari, Candra; Kurniawan, Imay; Singasatia, Dayan; Dian Safitri, Aulia (RISTEC : Research in Information Systems and Technology, 2024)
The decision support system is able to provide the best recommendations from existing alternatives based on calculation results. One method that can be implemented is the Weighted Product (WP) Method.  The Weigted Product method is a method whose solution uses multiplication to connect attribute values, where the value must be raised to the power of the weight value of the attribute in question. In the academic activities of a Senior High School (SMA), there are activities to select outstanding students. This activity aims to ensure that students who excel can become school representatives in various activities at the sub-district, regency, provincial and national levels. The criteria used in this research are average grades, attendance, attitudes and behavior, extracurriculars, and non-academics. The case study used a total of five alternatives. The implementation results show that the alternative with the highest V value calculation results, namely 0.238, can be recommended as an outstanding student.